Household studies in pastoral systems research - Grandin, B.E.; Bekure, S. (International Livestock Centre for Africa, 1983)
Reviews differences between crop production and pastoral production, considering their effects on research possibilities; and describes basic methods that may be used to collect household level data, esp. informal & formal surveys, enumeration and the use of questionnaires.